Clinical Ethics on Film A Guide for Medical Educators - Rosenthal, M. Sara (Springer International Publishing, 2018)
This book discusses feature films that enrich our understanding of doctor-patient dilemmas. The book comprises general clinical ethics themes and principles and is written in accessible language. Each theme is discussed and illuminated in chapters devoted to a particular film. Chapters start with a discussion of the film itself, which shares details behind the making of the film; box-office and critical reception; casting; and other facts about production. The chapter then situates the film in a history of medicine and medical sociology context before it delves into the clinical ethics issues in the film, and how to use it as a teaching aid for clinical ethics. Readers will understand how each film in this collection served to bring particular clinical ethics issues to the public's attention or reflected medico-legal issues that were part of the public discourse. The book is a perfect instructor's guide for anyone teaching bioethics, healthcare ethics, medical sociology, medical history, healthcare systems, narrative medicine, or nursing ethics.